Kompetensi Membaca Pemahaman Siswa SD di Indonesia: Studi Kasus Kelas III SDI Sultan Agung - Puspitaningrum, Endah Tri; Afandi, Muhammad; Sari, Yunita (IAIN Kendari, 2025)
This study aims to describe the reading comprehension ability of third-grade elementary school students and to identify the obstacles they face in understanding texts. The research employed a qualitative approach with a descriptive design. Data were collected through observation, oral tests, and in-depth interviews. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The findings indicate that students' reading comprehension ability falls into the